Effector genes in Magnaporthe oryzae Triticum as potential targets for incorporating blast resistance in wheat - Navia Urrutia, Monica; Mosquera, Gloria M.; Ellsworth, Rebekah; Farman, Mark; Trick, Harold N.; Valent, Barbara (Scientific Societies, 2022)
Wheat blast (WB), caused by Magnaporthe oryzae Triticum pathotype, recently emerged as a destructive disease that threatens global wheat production. Because few sources of genetic resistance have been identified in wheat, genetic transformation of wheat with rice blast resistance genes could expand resistance to WB. We evaluated the presence/absence of homologs of rice blast effector genes in Triticum isolates with the aim of identifying avirulence genes in field populations whose cognate rice resistance genes could potentially confer resistance to WB. We also assessed presence of the wheat pathogen AVR-Rmg8 gene and identified new alleles. A total of 102 isolates collected in Brazil, Bolivia, and Paraguay from 1986 to 2018 were evaluated by PCR using 21 pairs of gene-specific primers. Effector gene composition was highly variable, with homologs to AvrPiz-t, AVR-Pi9, AVR-Pi54, and ACE1 showing the highest amplification frequencies (>94%). We identified Triticum isolates with a functional AvrPiz-t homolog that triggers Piz-t–mediated resistance in the rice pathosystem and produced transgenic wheat plants expressing the rice Piz-t gene. Seedlings and heads of the transgenic lines were challenged with isolate T25 carrying functional AvrPiz-t. Although slight decreases in the percentage of diseased spikelets and leaf area infected were observed in two transgenic lines, our results indicated that Piz-t did not confer useful WB resistance. Monitoring of avirulence genes in populations is fundamental to identifying effective resistance genes for incorporation into wheat by conventional breeding or transgenesis. Based on avirulence gene distributions, rice resistance genes Pi9 and Pi54 might be candidates for future studies.